THE USE OF SOMATIC PHRASES IN NOVEL “BYGONE DAYS” (Modern education and development, 2025)
This article looks at the use of body-related phrases in Abdulla Qodiriy’s important novel, Bygone Days, which is the first complete Uzbek novel. It discusses how these somatic expressions enhance the story, express feelings, and reflect Uzbek cultural identity. By analyzing certain examples from the book, the study demonstrates how the use of body language helps with character development, provides social commentary, and supports cultural preservation. Additionally, the article talks about how studying somatic phrases can be useful in literature and linguistics courses in educational institutions in Uzbekistan.